LIVE STREAM CLASSROOMS DURING PANDEMIC 2020: COMPARATIVE STUDY OF THE PERCEPTION OF TEACHERS AND STUDENTS - Kainat; Sultan, Dr. Sohaib; Naureen, Dr. Shazia (The journal of contemporary issues in business and government, 2021)
Due to the pandemic situation of the COVID-19 the live stream had being adopted for online learning in higher education system of Pakistan. The bidirectional communication in live stream is synchronized connection via Internet, such as video-audio conferencing though the software of the Microsoft team, zoom, google meet and Skype had utilized for learning. The purpose of the research were to compare the perception of teachers and students regarding the live stream classrooms during outbreak covid-19. The study were significant to teachers, students, new researchers and policy makers. The study were descriptive survey method. The research were quantitative and questionnaire were utilized by researcher to collect the respondent’s responses. Whereas descriptive and inferential statistics were used to analyzed the data. The results of the study were depicted that mostly respondents were not satisfied though online live stream classrooms, there is no difference between the perception of the teachers and students regarding the live stream classrooms during outbreak covid-19. Students were not self-motivated and to maintain discipline in live sessions is very difficult for teachers as well. Technical issues had made class boring, cause the cognitive exertion and become time consuming. The subjects like science mathematics and engineering cannot taught properly. Learners can engage through video conferencing and interactive discussion. Moreover research recommended that teachers should trained for these techniques, advance applications should provide by Government for online learning, interactive discussion is the best way to engage learners in live stream. Discussion method may be used and video conferencing may be preferred.